Risk premium spillovers among stock markets: Evidence from higher-order moments - FINTA, Marinela Adriana (Institutional Knowledge at Singapore Management University, 2020)
We investigate the volatility and skewness risk premium spillovers among the U.S., U.K., German, and Japanese stock markets. We define risk premia as the difference between risk-neutral and realized moments. Our findings highlight that during periods of stress, cross-market and cross-moment spillovers increase and that these increases are mirrored by a decrease in within-market effects. We document strong bidirectional spillovers between volatility and skewness risk premia and emphasize the prominent role played by the volatility risk premium. Finally, we show that several announcements drive the time-varying risk premium spillovers.